Exploration of Local Knowledge of Ethnomedicine and Medicinal Plants on Nias Island - Dachi, Kanne; Tambunan, Ika Julianti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: The use of plants in Indonesia has been carried out for generations, especially as part of traditional medicine. This traditional medicine is still a very valuable national asset and continues to be used by communities throughout Indonesia. One of them is the Nias tribal community in North Sumatra, where around 50% of them still use and care for medicinal plants which are considered more effective and economical as treatment in their own environment. Objective: The aim of this research is to find out the various types of plants used by the people of Nias, North Sumatra, how they are processed, and which parts of the plants are used for medicine. Methode: The research method used is a combination of qualitative and quantitative methods which are explained descriptively. Data collection techniques include interviews, observation and documentation. Meanwhile, data analysis techniques include data collection, data condensation, data presentation, and drawing conclusions. Result: The research results showed that there were 46 types of medicinal plants obtained from the results of a questionnaire to the community, with a total of 20 informants from 5 villages spread across Nias Regency, North Sumatra. Traditional treatments still practiced by the people of Nias include boiling, squeezing, pounding, burning and soaking. The way it is served also shows a high level of knowledge about medicinal ingredients, such as drinking, sticking or applying, compressing, bathing, eating and applying. Conclusion: The reason for using this traditional medicine is because it is considered cheaper, easier, safer and has minimal side effects.